Trends over time and interhospital variation in the primary treatment approach for T1 colon carcinomas in the Netherlands - Hanevelt, Julia; van Erning, Felice N.; de Vos tot Nederveen Cappel, Wouter H; Vleggaar, Frank P.; van Westreenen, H L; Moons, Leon MG (Endoscopy, 2025)
This study evaluated the use of local resection as initial treatment vs. primary surgery for T1 colon carcinoma in the Netherlands over time, hospital variations, and whether changes in treatment approaches impacted 5-year relative and overall survival.This nationwide cohort study included patients diagnosed with pT1 colon adenocarcinoma in 2015–2022, identified from the Netherlands Cancer Registry. Multilevel, multivariable logistic regression models estimated the probability of undergoing local resection per hospital, adjusted for case-mix variables. Hospitals were categorized into low, average, or high attitude toward local resection. Relative and overall survival were calculated using multivariable regression analysis.9650 patients from 73 hospitals were included, with 3999 (41.4%) receiving primary surgery and 5651 (58.6%) undergoing local resection first. From 2015 to 2022, the proportion of primary surgery decreased from 53.2% to 29.7%. The adjusted relative risk for local resection varied across hospitals (0.46–1.29). No significant differences in 5-year relative or overall survival were found between high vs. low attitude centers (relative survival 99.0% vs. 97.7%, relative excess risk [RER] 0.97, 95%CI 0.51–1.84; overall survival 87.9% vs. 86.4%, adjusted hazard ratio [aHR] 0.95, 95%CI 0.81–1.11), nor between patients treated after vs. before 2018 (relative survival 98.7% vs. 98.7%, RER 0.82, 95%CI 0.46–1.46; overall survival 86.7% vs. 88.0%, aHR 0.98, 95%CI 0.85–1.13).While interhospital variation existed, local resection of T1 colon carcinoma was increasingly preferred in the Netherlands, leading to a reduction in surgery without a change in relative or overall survival.